A Proposal of a Method to Promote Creativity Based on Computational Thinking Using Modified Problem-posing - Fukui, Masanori (Universitas Muhammadiyah Purwokerto, 2024)
The development of creativity and computational thinking (CT) has been emphasized in education through various studies and research. In activities such as problem-based learning (PBL), students are required to set and solve problems independently. However, it is often difficult for them to discover problems independently, and for teachers to evaluate them appropriately. This study focused on activities where students created problems, that is, problem-posing and examined methods for demonstrating creativity based on CT. Using this method, students were asked to modify and improve the original problem based on CT. The advantages of this method are that it encourages students to understand the structure of the problem, allows them to create entirely new problems, and helps teachers evaluate their work properly.